On the hardy space H1 on products of half-spaces - Bertolo, Nativi Viana Pereira [UNESP] (Mathematical Sciences Publishers, 1989)
We show that the Hardy space Hanal1(R+2 × R+2) can be identified with the class of functions f such that f and all its double and partial Hubert transforms Hkf belong to L1(R2). A basic tool used in the proof is the bisubharmonicity of |F|q, where F is a vector field that satisfies a generalized conjugate system of Cauchy-Riemann type. © 1989 by Pacific Journal of Mathematics.